Detection of Porcine DNA in Cosmetic Products using Real-Time PCR Method: A Review of Method and Applications - Sari, Miftiana Nugraha; Sophian, Alfi; Nawwaruddin, Hazza Hammam; Rumiyati, Rumiyati; Rohman, Abdul (Journal of Food and Pharmaceutical Sciences, 2025)
For Muslim customers, the halal validity of cosmetics is a major concern. In cosmetics industry, one critical aspect is the contamination of porcine derivatives in halal cosmetic products. This review method discusses the application of real-time PCR (RT-PCR) for the detection of porcine DNA in cosmetic products, including the principle of the method, DNA extraction protocol, primers and probes design, and method application in various types of cosmetic products. DNA extraction from the cosmetic matrix samples requires optimization due to the complexity of the material and the possibility of DNA degradation during the cosmetic production process. The precise primers and probes design is also crucial to ensure specificity towards porcine DNA. The application of the RT-PCR method has been successful in various forms of cosmetics such as creams, lotions, lipsticks, and soaps, although each type of cosmetic product has unique challenges. Performance evaluation of the RT-PCR method showed good repeatability and reproducibility with coefficients of variation (CV) below 10% in numerous studies. The main challenges of the method include extraction of DNA due to the DNA degradation during the cosmetics production process, interference from cosmetic ingredients to RT-PCR analysis, and the need for method standardization. Solutions that have been developed such as the use of short gene targets, PCR additives to overcome inhibitors, and amplification techniques such as digital PCR to improve sensitivity. The recent development has led to the integration of protein-based methods and international standardization to support cosmetic halal certifications.